1997
DOI: 10.1021/jp963835y
|View full text |Cite
|
Sign up to set email alerts
|

The SAM Model for Wear Inhibitor Performance of Dithiophosphates on Iron Oxide

Abstract: Zinc dithiophosphate (DTP) molecules have long been used as wear inhibitor oil additives for automotive engines. In order to obtain an atomistic understanding of the mechanism by which these molecules inhibit wear, we examined the geometries, energetics, and vibrations of an oxidized iron surface [(001) surface of α-Fe2O3] using the MSX force field (FF) based on ab initio quantum chemistry (QC) calculations. The DTP molecules studied include (RO)2PS2 with R = methyl, isobutyl, isopropyl, and phenyl. The α-Fe2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 15 publications
2
61
0
2
Order By: Relevance
“…The molecular dynamics of oil and water phase flow over chemically modified clay surfaces can form the basis for a rational design of hydrodynamic surface modifiers in the same way that the modeling of organic additives on metal surfaces has helped the discovery of novel metal wear inhibitors. 27,28 Clays in nature are usually covered with other minerals and organic substances, organic-cementing agents, consisting of proteinaeceous and humic materials, 32 C 6 -C 30 methyl esters of aliphatic and aromatic acids, and methoxy derivatives of phenols and phenolic acids. 33 In real reservoir applications, these compounds must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular dynamics of oil and water phase flow over chemically modified clay surfaces can form the basis for a rational design of hydrodynamic surface modifiers in the same way that the modeling of organic additives on metal surfaces has helped the discovery of novel metal wear inhibitors. 27,28 Clays in nature are usually covered with other minerals and organic substances, organic-cementing agents, consisting of proteinaeceous and humic materials, 32 C 6 -C 30 methyl esters of aliphatic and aromatic acids, and methoxy derivatives of phenols and phenolic acids. 33 In real reservoir applications, these compounds must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The function of many lubricant additives depends on chemical reactions, which are generally not considered in classical MD simulations. Despite this, classical MD simulations have given unique insights into the behaviour of a range of lubricant additives including detergents [207,208], dispersants [209,210], viscosity modifiers [91,92,211], anti-wear additives [212][213][214][215], and corrosion inhibitors [216][217][218]. The most widely studied class of lubricant additives with MD are friction modifiers [219], which are a wellsuited application of confined NEMD simulations.…”
Section: Nemd Simulations Of Lubricant Additivesmentioning
confidence: 99%
“…The inclusion of the vacuum space into the unit cell was done to avoid an artificial influence from periodic images in the z direction. [19][20][21] Spohr 21 compared the results from this approach with those from the two-dimensional Ewald summation ͑eW2D͒ method which was first introduced by Parry 9 and later independently derived by Heyes, Barber, and Clarke. 10 It was concluded that results for this approach converged to those of EW2D when the vacuum height was large in the z direction.…”
Section: ͑8͒mentioning
confidence: 99%
“…Figure 2 shows that potential energy and RMS force in dendrimer systems converge within a certain range of vacuum height in the z direction using the EW3D technique. 20,21 According to Spohr 21 and Jorge and Seaton, 27 the conventional EW3D technique with an appropriate vacuum space in the z direction reproduced EW2D results with an energy error of less than 1%, but it is still quite time consuming. Since the EW3D as applied to quasi-2D is our reference and its error in energy as compared to strict EW2D is within 1%, a comparison between our CMM2D and this reference is not as strict as in 3D systems.…”
Section: B MD Simulations Of Confined Systemsmentioning
confidence: 99%